(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Ameobiasis is an infection caused by Entamoeba histolytica, which is a serious problem especially in developing countries and ranks third among the parasitic infections that lead to death mostly in primary age children.The aim of the present study was to investigate the prevalence of E. histolytical in young children.Three hundred (300) children aged 0-14 years were sampled for E. histolytica infection in five rural communities in Wushishi Local Government Area, Niger State, North Central Nigeria. The stool samples were examined for cysts of E. histolytica using saline and iodine preparations. The prevalence rate of 17 % was recorded. The prevalence by sex had a higher infection rate in males (19.3 %) than females (14.6%) which was not significantly (P>0.05). The prevalence of the infection in relation to age was highest (23%) in 7 to 10 year age group, while the least infection of 12 (12%) was recorded in 11 to 14 year age group A significant association was found between the sources of drinking water and prevalence of E. histolytica (P<0.05). The highest was recorded in those using stream/pond (89.2%) and least recorded from Borehole/Tap (40.3%). Therefore, it become necessary need for improved sanitation, personal hygiene, health education policy and a proper deworming scheme amongst school children in the study areas in order to decrease infections rate.